MODEL RAPID APPLICATION DEVELOPMENT UNTUK RANCANG BANGUN SISTEM PENGELOLAAN TRANSAKSI PERDAGANGAN INDOSURRATI SUKSES MAKMUR (INTI Nusa Mandiri, 2023)
The problem of manual recording is one of the problems that is often experienced by small and medium-scale businesses such as MSMEs, this occurs along with the increasing quantity of transactions, a large number of items of goods, and the growth and development of businesses, including PT. Surrati Sukses Makmur is engaged in the retail sale of perfume products. This problem can have negative impacts, such as difficulties in monitoring stock so that discrepancies easily occur, transactions not recorded so that data is lost, preparation of reports taking more time, fraud, and the need for a place to store documents. To overcome this problem, it is necessary to analyze and design a digital-based sales information system that can help the process of recording sales to be more efficient, accurate, safe, and easy. By using a digital information system, there is no need for a special place for document storage, loss of transaction data can be minimized so that it has an impact, PT. Surrati Sukses Makmur can improve performance and quality of service to customers, as well as operational costs can be reduced and inventory management can be easier. The design of this system uses the Rapid application Development (RAD) model with the aim that applications can be completed immediately and reduce the cost of making application systems so that reports can be made in a comprehensive and effective and efficient manner, , as well as with the black-box testing method in testing the application can be used more effectively and efficiently, and as a whole is in accordance with system requirements
Keywords: Digital Sales Transactions; RAD Model System; Trade Transaction Management System; Black-box Testing